Cortical inflammation and brain signs of high-risk atherosclerosis in a non-human primate model. Issue 2 (1st April 2021) - Di Cataldo, Vanessa; Debatisse, Justine; Piraquive, Joao; Géloën, Alain; Grandin, Clément; Verset, Michaël; Taborik, Fabrice; Labaronne, Emmanuel; Loizon, Emmanuelle; Millon, Antoine; Mury, Pauline; Pialoux, Vincent; et al.
Abstract: Atherosclerosis is a chronic systemic inflammatory disease, inducing cardiovascular and cerebrovascular acute events. A role of neuroinflammation is suspected, but not yet investigated in the gyrencephalic brain and the related activity at blood−brain interfaces is unknown. A non-human primate model of advanced atherosclerosis was first established using longitudinal blood samples, multimodal imaging and gene analysis in aged animals. Non-human primate carotid lesions were compared with human carotid endarterectomy samples. During the whole-body imaging session, imaging of neuroinflammation and choroid plexus function was performed. Advanced plaques were present in multiple sites, premature deaths occurred and downstream lesions (myocardial fibrosis, lacunar stroke) were present in this model. Vascular lesions were similar to in humans: high plaque activity on PET and MRI imaging and systemic inflammation (high plasma C-reactive protein levels: 42 ± 14 µg/ml). We also found the same gene association (metabolic, inflammatory and anti-inflammatory markers) as in patients with similar histological features. Metabolic imaging localized abnormal brain glucose metabolism in the frontal cortex. It corresponded to cortical neuro-inflammation (PET imaging) that correlated with C-reactive protein level. Multimodal imaging also revealed pronounced choroid plexus function impairment in aging atherosclerotic non-human primates. In conclusion, multimodal whole-body inflammation exploration at the vascular level and blood−brain interfaces identified high-risk aging atherosclerosis. These results open the way for systemic and central inflammation targeting in atherosclerosis in the new era of immunotherapy. Abstract : Elevated cortical inflammation and defective choroid plexus activity associate with high-risk atherosclerosis in cynomolgus monkeys. Using diet-induced atherosclerosis, in-vivo imaging and gene analysis, Di Cataldo et al. showed (i) monkeys exhibit similar atherosclerosis features and vulnerable plaques-associated genes as patients, (ii) brain imaging demonstrated frontal cortex neuroinflammation and neurovascular signs. Graphical Abstract: